Networks and Hierarchies: Two Ways of Thinking - Moor, Argo; Luks, Leo (Problemos, 2015)
The main motive of the 20th century continental philosophy was criticism of metaphysics. Previous philosophical systems were considered too rigid; there was a search for a way out from metaphysical hierarchical way of thinking. Using the synthesis of the history of religions and philosophy, this paper claims that many surprising similarities can be found between animism and the lines of thought of the 20th century philosophy. The paper analyses the differences between network thinking and hierarchical thinking. Network thinking is analysed through two motives: multidimensionality and the network of shared souls. Animism is used as a major example to describe the impact of motives to thinking and practices. The rise and spread of hierarchical thinking is also described.
Keywords: 20th century philosophy; history of religions; hierarchical thinking; network thinking; animism